2011
DOI: 10.1161/circulationaha.110.957373
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Timing of Chronic Preoperative Aspirin Discontinuation on Morbidity and Mortality in Coronary Artery Bypass Surgery

Abstract: Background— Aspirin (ASA) has been shown to reduce postoperative coronary artery bypass grafting (CABG) mortality and ischemic events; however, the timing of chronic ASA discontinuation before surgery is controversial because of concern about postoperative bleeding. We evaluated the effect of the timing of ASA discontinuation before CABG on major adverse cardiovascular outcomes and postoperative bleeding using the Cleveland Clinic Cardiovascular Information Registry database. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 23 publications
2
40
1
3
Order By: Relevance
“…2 Professional organizations differ in their recommendations, 18 -20 with some recommending stopping 3 to 5 days before surgery and others recommending 7 to 10 days. The present report by Jacob and colleagues 21 indicate that late (within 5 days of CABG) discontinuation of aspirin is not associated with any measurable differences in thrombotic complications after CABG when compared with early (at least 6 days before CABG) discontinuation. Rates of a composite outcome that included in-hospital myocardial infarction, stroke, and mortality were comparable between groups: 1.7% versus 1.8%; Pϭ0.8.…”
Section: Article See P 577contrasting
confidence: 39%
“…2 Professional organizations differ in their recommendations, 18 -20 with some recommending stopping 3 to 5 days before surgery and others recommending 7 to 10 days. The present report by Jacob and colleagues 21 indicate that late (within 5 days of CABG) discontinuation of aspirin is not associated with any measurable differences in thrombotic complications after CABG when compared with early (at least 6 days before CABG) discontinuation. Rates of a composite outcome that included in-hospital myocardial infarction, stroke, and mortality were comparable between groups: 1.7% versus 1.8%; Pϭ0.8.…”
Section: Article See P 577contrasting
confidence: 39%
“…[8,9,24]. In contrast, there is research supporting discontinuation of aspirin before cardiac operations [10]. In our study, we found that in patients undergoing CABG only, preoperative aspirin use was not associated with risks of MACE, postoperative renal failure, 30-day mortality, reoperation for bleeding, blood transfusion, or postoperative infection.…”
Section: Aspirin Use In Patients Undergoing Valve Operations Onlymentioning
confidence: 47%
“…In the postoperative period, early aspirin therapy has been consistently reported to improve clinical outcomes for patients undergoing coronary artery bypass grafting (CABG), including better graft patency [3][4][5][6] and a reduced risk of death and ischemic complications [7]. However, whether aspirin should be used in the preoperative period remains controversial [8][9][10][11][12][13]. Several studies showed lower mortality [8,9] in patients undergoing CABG, whereas others found a similar mortality rate and higher transfusion requirement [10,[14][15][16][17].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we recommend weighing the risks and benefits of late aspirin use in these patients. 6 onset from 2003 to 2009 in 1082 hospitals participating in the Get With the Guidelines-Stroke Program were analyzed to determine frequency, patient and hospital characteristics, and temporal trends in patients treated with door-to-needle times Յ60 minutes. Only 26.6% of tPA-treated patients had a door-to-needle time Յ60 minutes.…”
Section: Effect Of Timing Of Chronic Preoperative Aspirin Discontinuamentioning
confidence: 99%